Cover Image, Volume 28, Issue 1. Issue 1 (20th December 2017) - Kozareva, Danka A.; O'Leary, Olivia F.; Cryan, John F.; Nolan, Yvonne M.
Abstract : Cover legend: This cover image, by Danka A. Kozareva et al., is based on the Rapid Communication Deletion of TLX and social isolation impairs exercise-induced neurogenesis in the adolescent hippocampus, DOI:10.1002/hipo.22805 .